Pengaruh Lingkungan Keluarga dan Keaktifan Berorganisasi Terhadap Perilaku Beragama Pada Remaja di Kecamatan Srandakan Bantul Yogyakarta - Erbaningrum; Ru'iya, Sutipyo (Akhlaqul Karimah: Jurnal Pendidikan Agama Islam, 2026)
This study aims to determine the influence of family environment and active participation in organizations on the religious behavior of adolescents in Srandakan District, Bantul, Yogyakarta. This research method uses quantitative research with an associative approach. The subjects were 81 adolescent mosque attendees in Gunturgeni Village, Poncosari. Data collection techniques used questionnaires regarding family environment, activity as an adolescent mosque attender, and religious behavior. Data analysis used simple linear regression and multiple linear regression analysis. The results of the simple linear regression analysis indicate a 57.0% influence of family environment on adolescent religious behavior, and 63.6% influence of organizational activity on religious behavior. The multiple regression analysis shows that the joint influence of family environment and organizational activity on religious behavior is 71.1%. Based on the above findings, it is recommended to improve the vibrancy of the family environment and encourage adolescents to be active in organizations in their respective neighborhoods, so that their religious behavior improves. Good religious behavior will create a positive life in the community.